2023
DOI: 10.3390/ijms24043819
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin II Enhances Advanced Aortic Atherosclerosis Formation and Delays Plaque Regression in Hyperlipidemic Rabbits

Abstract: Accumulated evidence shows that elevated urotensin II (UII) levels are associated with cardiovascular diseases. However, the role of UII in the initiation, progression, and regression of atherosclerosis remains to be verified. Different stages of atherosclerosis were induced in rabbits by a 0.3% high cholesterol diet (HCD) feeding, and either UII (5.4 μg/kg/h) or saline was chronically infused via osmotic mini-pumps. UII promoted atherosclerotic fatty streak formation in ovariectomized female rabbits (34% incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…It has been reported that rabbit macrophages and human vascular endothelial cells were induced to secrete VEGF by U II, 18,19 suggesting that U II is likely to be an important factor in promoting VEGF secretion from DPCs. To confirm the effect of U II on the VEGF secretion from DPCs, the concentration of VEGF in the supernatant of DPCs cultured medium was detected by ELISA.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that rabbit macrophages and human vascular endothelial cells were induced to secrete VEGF by U II, 18,19 suggesting that U II is likely to be an important factor in promoting VEGF secretion from DPCs. To confirm the effect of U II on the VEGF secretion from DPCs, the concentration of VEGF in the supernatant of DPCs cultured medium was detected by ELISA.…”
Section: Discussionmentioning
confidence: 98%
“…U-II expression is often found to be increased in atherosclerotic lesions in the coronary and carotid arteries and aorta. 16 Accordingly, it was suggested that elevated expression of U-II leads to vascular smooth muscle proliferation, accelerating the development of atherosclerotic plaque. In addition, it was shown that locally released U-II leads to coronary vasoconstriction and myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%